Perceiving the Character Development of Dickon Sowerby in Burnett’s The Secret Garden based on Watson’s Behaviorist Theory - Maghfiroh, Hanim; Amri, M. Misbahul; Masduqi, Harits; Chotib, Mochamad Nasrul (Alphabet, 2024)
This study delves into the character development of Dickon Sowerby, a child character in Frances Hodg-son Burnett's novel, The Secret Garden. As a supporting character to Mary Lennox and Colin Craven, the study explores Dickon's characterization using Watson's behaviorist theory to analyze observable behavior and environment in children's developmental processes. The analysis draws from dialogue and narration related to Dickon's character, examining his behavior towards family, neighbors, and nature's wild crea-tures. Additionally, the study looks at the influence of Dickon's home, consisting of parents and siblings, as well as the neighborhood's moorland, which serves as the heath.